Importance of the Principles of the Government Procurement (2016)
In public administration there is a major issue, public procurement which consists of contracts awarded for work and work in government agencies in order to benefit society, this recruitment process has several stages ranging from studies of work to be done, establish requirements for individuals or companies that can perform them, the way of choice of contractors with the allocation of the project to the person or ideal company for implementation, this process should take into account several aspects such as the principles of government procurement, which seek to ensure that these processes are transparent procurement and provide the same conditions of opportunity for all people who want to run these contracts